2017
DOI: 10.5194/bg-14-177-2017
|View full text |Cite
|
Sign up to set email alerts
|

Role of zooplankton in determining the efficiency of the biological carbon pump

Abstract: The efficiency of the ocean's biological carbon pump (BCP eff -here the product of particle export and transfer efficiencies) plays a key role in the air-sea partitioning of CO 2 . Despite its importance in the global carbon cycle, the biological processes that control BCP eff are poorly known. We investigate the potential role that zooplankton play in the biological carbon pump using both in situ observations and model output. Observed and modelled estimates of fast, slow, and total sinking fluxes are present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 60 publications
2
59
1
Order By: Relevance
“…Microbial respiration of fast‐sinking POC flux is often found to be too slow to explain observed decreases in flux [ Belcher et al ., ] which suggests that zooplankton processing may have significant interactions with fast‐sinking particles. Several recent papers have concluded that zooplankton sloppy feeding [ Giering et al ., ], microbial gardening [ Mayor et al ., ], and zooplankton fragmentation [ Cavan et al ., ; Belcher et al ., ; Cavan et al ., ] may lead to the in situ production of slow‐sinking particles from fast‐sinking particles.…”
Section: Resultsmentioning
confidence: 99%
“…Microbial respiration of fast‐sinking POC flux is often found to be too slow to explain observed decreases in flux [ Belcher et al ., ] which suggests that zooplankton processing may have significant interactions with fast‐sinking particles. Several recent papers have concluded that zooplankton sloppy feeding [ Giering et al ., ], microbial gardening [ Mayor et al ., ], and zooplankton fragmentation [ Cavan et al ., ; Belcher et al ., ; Cavan et al ., ] may lead to the in situ production of slow‐sinking particles from fast‐sinking particles.…”
Section: Resultsmentioning
confidence: 99%
“…While the observed seasonality in small‐particle transfer efficiency is likely driven in large part by changes in stratification, it may also reflect changes in particle consumption. For example, increased summertime zooplankton abundance and metabolism might reduce particle export through grazing activities (Cavan et al, ). Alternatively, the microbial community could display an increased abundance or increased remineralization rates due to increased temperatures observed in the upper mesopelagic in summer (Rivkin & Legendre, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mari et al [] show that transparent exopolymer particles (TEPs) accumulate in the surface microlayer and need to be ballasted to overcome its low density and to promote aggregation, which brings into question the classic view that TEP increases POC flux by promoting aggregation through its role as a “biological glue.” Attenuation of POC flux is also affected by surface processes that modify the character and lability of the POC that is exported. In this context, episodic events [ Lebrato et al , ; Smith et al , ], community structure [ Guidi et al , ; Guidi et al , ], and zooplankton processes [ Giering et al , ; Cavan et al , , ; Steinberg and Landry , ] are all likely important.…”
Section: Discussionmentioning
confidence: 99%